Taxonomic revision of Neotropical Phyllocnistis Zeller, 1848 (Lepidoptera: Gracillariidae), with descriptions of seven new species and host plant associations - Brito, Rosângela; Lopez-Vaamonde, Carlos; Gonçalves, Gislene L.; Becker, Vitor O.; Mielke, Olaf H.h.; Moreira, Gilson R. P. (Zootaxa, 2017)
Until now, 20 species of leaf-mining micromoths of the genus Phyllocnistis Zeller (Lepidoptera, Gracillariidae) have been known to occur in the Neotropical region. Here we revise the previously known species and describe seven new species: four from French Guiana, P. kawakitai Brito & Lopez-Vaamonde, sp. nov., P. norak Brito & Lopez-Vaamonde, sp. nov., P. ohshimai Brito & Lopez-Vaamonde, sp. nov., P. petronellii Brito & Lopez-Vaamonde, sp. nov.; and, three from Brazil, P. helios Brito & Moreira, sp. nov., P. jupiter Brito & Moreira, sp. nov. and P. xylopiella Brito & Becker, sp. nov. Lectotypes are designated for P. aurilinea Zeller, 1877; P. citrella Stainton, 1856; P. rotans and P. sexangula Meyrick, 1915. Detailed descriptions of the pattern of forewing fasciae are provided for all species. Host plant associations, photographs of adults and illustrations of genitalia, when available, are provided for the described species of Neotropical Phyllocnistis. In addition, DNA barcodes were used for the delimitation of some species.